Addressing Defenses in Psychotherapy to Improve Adaptation. Issue 3 (3rd April 2017) - Perry, J. Christopher; Bond, Michael
ABSTRACT: Defense mechanisms have a robust history in psychoanalysis and psychodynamic theory, research and practice. Defense mechanisms are one's automatic adaptive responses to internal and external threat and conflict. Evidence suggests that they affect symptoms and functioning. When defenses are examined during treatment, improvement in defensive functioning is associated with subsequent improvement in symptoms and functioning. Change in defenses appears to play a fundamental mediating role in change overall. This article reviews data from studies on defense mechanisms and presents a case that displays the role of the therapist in addressing defenses and how both supportive and interpretive interventions work together to improve defensive functioning. This and other evidence suggest that working to improve defensive functioning may mediate improvement in other aspects of experience and psychosocial functioning. Working with defenses may play a fundamental role in treatment, which warrants further study.